Optimisation of a Multi-Element Airfoil for a Fixed-Wing Airborne Wind Energy System - Agustí Porta Ko; Sture Smidt; Roland Schmehl; Manoj Mandru (Energies, 2023)
Airborne wind energy systems benefit from high-lift airfoils to increase power output. This paper proposes an optimisation approach for a multi-element airfoil of a fixed-wing system operated in pumping cycles to drive a drum-generator module on the ground. The approach accounts for the different design objectives of the tethered kite’s alternating production and return phases. The airfoil shape is first optimised for the production phase and then adapted for the requirements of the return phase by modifying the flap setting. The optimisation uses the multi-objective genetic algorithm NSGA-II in combination with the fast aerodynamic solver MSES. Once the optimal shape is determined, the aerodynamic performance is verified through CFD RANS simulations with OpenFOAM. The resulting airfoil achieves satisfactory performance for the production and return phases of the pumping cycles, and the CFD verification shows a fairly good agreement in terms of the lift coefficient. However, MSES significantly underpredicts the airfoil drag.